The dilemma of using physical restraint in delirium tremens: a case report - Malik, Yogender Kumar; Basu, Debasish; Naskar, Chandrima (International Journal of Research in Medical Sciences, 2019)
Delirium tremens (DT) is a common presentation in tertiary care hospitals. Refractory DT, though not very common, is a dreaded presentation in any clinical setting. Usually, patients with DT respond to standard doses of benzodiazepines, but sometimes we encounter patients requiring higher than the usual dose. Also, due to the high level of agitation, confusion and hallucinatory behaviour, physical restraint is frequently used in these patients. We hereby report a case of refractory DT in whom the dilemma of using physical restraint and need for higher doses of Benzodiazepine has been highlighted.